2010
DOI: 10.1042/cbi20090009
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of the extreme C‐terminal end of the S6 inner helix in C‐terminal‐truncated Kv1.2 channel activation

Abstract: The transmembrane part of the S6 inner helix of the Kv1.2 potassium channel is a pivotal part in sustaining channel activity. However, the role of its extreme C-terminal end, which is located on the cytoplasmic side of the channel, is largely unknown. Here, we investigated the role of the extreme C-terminal end of the S6 inner helix (the HRET region) by constructing a series of C-terminal-truncated mutations related to this region in the C-terminal-truncated Kv1.2 channel. Mutations on Thr421 or Glu420 signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…This finding highlights that trafficking motifs may not be universal and their importance must be tested for each channel/expression system combination. A similar conclusion can be drawn for the role of the HRET sequence in regulating channel conductance 12 , 49 : in case of Kv1.3 even an alanine substitution of the HRETE sequence restored channel function. Based on this and other recent papers the presence of the C-terminal amino acids adjacent to the activation gate in Kv1.3 are important for maintaining ion conductance, whereas distant C-terminal amino acids govern interactions with other proteins or confer cholesterol sensitivity to the Kv1.3 50 .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This finding highlights that trafficking motifs may not be universal and their importance must be tested for each channel/expression system combination. A similar conclusion can be drawn for the role of the HRET sequence in regulating channel conductance 12 , 49 : in case of Kv1.3 even an alanine substitution of the HRETE sequence restored channel function. Based on this and other recent papers the presence of the C-terminal amino acids adjacent to the activation gate in Kv1.3 are important for maintaining ion conductance, whereas distant C-terminal amino acids govern interactions with other proteins or confer cholesterol sensitivity to the Kv1.3 50 .…”
Section: Discussionsupporting
confidence: 70%
“…The HRET(E) is sequence is located in the part of the C-terminal that is proximal to the activation gate or may be part of it 49 . Thus, mutation in this region may profoundly alter activation gating of the channels, the coupling of the voltage-sensor movement to the activation gate or both while leaving the voltage-sensor movement intact.…”
Section: Discussionmentioning
confidence: 99%
“…We note that near the gate there is a histidine (H418 in the 3Lut numbering) on the C terminal end of the pore helix S6, which could affect gating if charged. If this histidine is deleted, the channel stops functioning [ 142 ].…”
Section: Gating Model From the Computationmentioning
confidence: 99%
“…Although the primary emphasis of this work concerns the relation of water structure to conduction, it also brings implications for gating. In earlier work ( 9) we showed that a residue below the gate, H418, when protonated, rotated toward the gate, with the histidine side-chain moving up almost 3 Å ; we summarized arguments for the importance of protonation, which changes both the potential at the gate and (not yet calculated, but very probably) the arrangement of water all the way from that residue to the gate (a D418 mutant does not function as a channel (36), so it appears that H418 must be important in structuring the channel to allow conduction). From the previous calculation, protonation of H418, and possibly two neighboring glutamates, should close the channel.…”
Section: Implications For Gatingmentioning
confidence: 89%